2020
DOI: 10.1523/jneurosci.0045-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced Inhibitory/Excitatory Responses in the Substantia Nigra Pars Reticulata Underlie Cannabinoid-Related Slowness of Movements

Abstract: The substantia nigra pars reticulata (SNr), where the basal ganglia (BG) direct and indirect pathways converge, contains among the highest expression of cannabinoid receptor type 1 (CB1r) in the brain. Hence, SNr is an ideal locus to study pathway interactions and cannabinergic modulations. The objective of this study was to characterize the effects of systemic injections of the CB1r agonist (CP55940) on the balanced activity of the direct/indirect pathways in the SNr and its associated behaviors. To this aim,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…First, in naïve behaving mice, briefly accustomed to our recording conditions, we found that cortical inputs to the VL/VM evoked complex stereotypical responses organized as transient activations and inactivations with a variety of response latencies (Figure 1). At first sight, these patterns were very similar to the ones previously reported for the sensorimotor cortex, striatum, and SNr in anesthetized rats (Báez-Cordero et al, 2020;Hidalgo-Balbuena et al, 2019;Peña-Rangel et al, 2021), suggesting a common responsive organization distributed throughout the thalamo-corticalBG sensorimotor loops. These responses could be classified into four stereotypical patterns present in a large proportion of the VL/VM population and observed in virtually all recorded animals (Figure 3).…”
Section: Discussionsupporting
confidence: 88%
“…First, in naïve behaving mice, briefly accustomed to our recording conditions, we found that cortical inputs to the VL/VM evoked complex stereotypical responses organized as transient activations and inactivations with a variety of response latencies (Figure 1). At first sight, these patterns were very similar to the ones previously reported for the sensorimotor cortex, striatum, and SNr in anesthetized rats (Báez-Cordero et al, 2020;Hidalgo-Balbuena et al, 2019;Peña-Rangel et al, 2021), suggesting a common responsive organization distributed throughout the thalamo-corticalBG sensorimotor loops. These responses could be classified into four stereotypical patterns present in a large proportion of the VL/VM population and observed in virtually all recorded animals (Figure 3).…”
Section: Discussionsupporting
confidence: 88%
“…We previously described a novel task where rats are trained to perform bilaterally coordinated movements with the forelimbs to obtain rewards ( Fig. 1A ) ( 36 ). Briefly, animals were trained to simultaneously displace two levers vertically, one with each forepaw ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used a bimanual coordination task as previously described ( 36 ). Animals were trained to hold the two levers, one with each paw, and to vertically displace them at least 2.6 cm (vertical threshold) for a fixed time threshold (50, 500, and 750 ms) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Through its distinct projections, it regulates movement control, decision making, consummatory activity, arousal and sleep states, initiation of epilepsy, threat avoidance, etc. 2,5,13,37,47,53,58 In the literature, SNr neurons are reported to respond diversely to various pain modalities, and using pharmacological or electrical neuromodulation to, respectively, inhibit or stimulate the SNr produces analgesic effects. 14 However, a consensus on how SNr neurons regulate pain perception has not yet been reached owing to technical limitations associated with these previous studies.…”
Section: Discussionmentioning
confidence: 99%